The lncRNA PVT1/miR-590-5p/FSTL1 axis modulates the proliferation and migration of airway smooth muscle cells in asthma - Wen-Lan Wang; Xiao-Ming Luo; Qin Zhang; Hai-Qiao Zhu; Guo-Qing Chen; Qin Zhou (Taylor & Francis Group, 2021)
Objective Asthma is a prevalent chronic inflammatory airway disease that is characterised by airway remodelling and airway hyperresponsiveness. Abnormal proliferation and migration of airway smooth muscle cells (ASMCs) contribute to airway remodelling in asthma. However, the molecular mechanism underlying an increased ASMC mass in asthma remains elusive. Herein, we aimed at investigating the regulation of lncRNA PVT1 on ASMCs and focussing on the mechanism in the proliferation and migration. Methods Expression levels of lncRNA PVT1 and miR-590-5p in the serum collected from 24 children with asthma and 10 control children were determined by qRT-PCR. ASMCs proliferation and migration prior to and post platelet-derived growth factor subunit B (PDGF-BB) stimulation were examined by CCK-8 test and transwell assay. Dual-luciferase reporter assay was performed to determine miR-590-5p interaction with lncRNA PVT1 and follistatin-like 1 (FSTL1). Expression of lncRNA PVT1, miR-590-5p, FSTL1, C-Myc, cyclin D1, and cyclin-dependent kinase 1 (CDK1) was tested by quantitative real-time PCR (qRT-PCR) and immunoblotting analysis. Results The expression level of lncRNA PVT1 was higher but the expression level of miR-590-5p was lower in the serum of children with asthma than in control children. The expression level of lncRNA PVT1 was negatively correlated with the expression level of miR-590-5p in asthma. LncRNA PVT1 was upregulated upon PDGF-BB stimulation. LncRNA PVT1 knockdown by its specific shRNA repressed PDGF-BB-induced promotion of proliferation and migration in ASMCs and triggered an elevated miR-590-5p along with declined C-Myc, cyclin D1, and CDK1. The effects of lncRNA PVT1 knockdown on PDGF-BB-induced ASMCs were lost upon miR-590-5p inhibition. MiR-590-5p targeted FSTL1 gene and declined its expression, thus suppressing ASMC proliferation and migration following PDGF-BB stimulation and downregulating C-Myc, cyclin D1, and CDK1 expressions. The effects of miR-590-5p on PDGF-BB-induced ASMCs were lost upon FSTL1 overexpression. Conclusion These results support the notion that the lncRNA PVT1/miR-590-5p/FSTL1 axis modulates ASMCs proliferation and migration following PDGF-BB stimulation, providing a potential therapeutic target to attenuate airway remodelling in asthma.